Contributi italiani al XIII Congresso internazionale degli Slavisti : (Ljubljana 15-21 agosto 2003) - Alberto Alberti; Marcello Garzaniti; Stefano Garzonio (Firenze University Press, 2014)
The Italian contributions to the XIII International Congress of Slavists (Ljubljana, 15-21 August 2003) had a very limited circulation between the participants in the congress and the restricted circle of experts. Considering the high scientific value of the individual contributions, to which we continue to refer in the framework of Slavic literature, it was decided to publish these acts in the series "Library of Slavic Studies" also to celebrate the ten years of its existence. Faced with a consolidated tradition of studies in the philological and literary field, Italian Slavistics of the beginning of the millennium found itself facing new needs. On the one hand, a new generation of linguists has established themselves, who have developed a series of innovative research on Slavic languages, especially in the contrastive field. On the other hand, new research paths have developed in contemporary literature, especially in relation to the most recent historical circumstances which have seen profound cultural transformations in the Slavic countries themselves, with the need to reconstruct consolidated literary canons also on the basis of the literature of emigration. The same philological research has been able to question itself again on its role by taking up in a different form traditional issues such as the Cyril-Methodian question, the problem of biblical citations or the debate on the Latin Slavia and the Orthodox Slavia, as well as the more traditional ecdotic issues manifesting a new sensitivity starting from religious issues. Alberto Alberti is researcher in Slavistics at the University of Bologna.